2008
DOI: 10.1021/ie800361a
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Isotopic Study of Ethane Dehydrogenation over a Semicommercial Pt,Sn/Mg(Al)O Catalyst

Abstract: Mechanistic and kinetic information on the ethane dehydrogenation reaction over a semicommercial Pt,Sn/ Mg(Al)O catalyst has been elucidated from catalytic testing and isotopic labeling experiments under reaction conditions close to those used in the commercial dehydrogenation process (C 2 H 6 /H 2 /H 2 O/inert ) 10/1.5/2/32 or C 2 H 6 /H 2 /CO 2 /inert ) 10/2/5/83, 600-630°C reaction temperature, atmospheric pressure). From kinetic measurements, a negative dependence of the reaction rate in H 2 and C 2 H 4 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…Alternatively, active metals may be deposited onto the LDH-derived supports via conventional impregnation techniques, as in the welldescribed Pt-Sn/Mg(Al)O x system. [19][20][21][22] Since many applications for LDH-derived materials have already emerged, with more expected to come, deeper insight into their chemistry is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, active metals may be deposited onto the LDH-derived supports via conventional impregnation techniques, as in the welldescribed Pt-Sn/Mg(Al)O x system. [19][20][21][22] Since many applications for LDH-derived materials have already emerged, with more expected to come, deeper insight into their chemistry is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…The most active catalyst for ethane dehydrogenation is platinum; however, in its pure form, it exhibits low ethene selectivity and rapid coke deposition, which contributes to catalyst deactivation [6]. Isotopic studies have revealed that both methane formation and coke accumulation originate from ethene re-adsorption and dehydrogenation [6,7]. The addition of a second metal, such as tin, indium, or gallium, to platinum has been found to be effective in increasing ethene selectivity and suppressing coke formation [6,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Moreover, ethane dehydrogenation into ethylene is central for polyethylene production. 10 Accounts reporting heavy hydrocarbon formation from CH 4 are predominantly based upon supported metal systems. [11][12][13] For instance Re and Mo supported on H-ZSM-5 convert CH 4 mainly to aromatics, with the selectivity to C 2 H 6 being less than 7%.…”
mentioning
confidence: 99%